Development of a linear micro actuator for ultra-precision positioning (Vol.2) - Du, Hejun (2008)
There is a strong demand for ultra-high precision positioning devices in many modern precision machines and devices, such as hard disk drives, CD/LD devices, wafer fabrication machines, optical fibre devices and measurement/testing equipment of micro devices. The requirement for resolution or positioning accuracy leaped quantumly from micron level to sub-micron, and subsequently to nano level. In addition to the ever-rising demand for high resolution, there is also strong demand for relatively large range gross motion so that the current two tiers coarse/fine positioning technology can be replaced by the more efficient single tier ultra-precision positioning actuators. Such high precision actuators of nano-level resolution can be made possible by using smart materials based actuators and microelectromechanical system (MEMS) technology.